Global and regional potential of wastewater as a water, nutrient and energy source - Qadir, Manzoor; Drechsel, Pay; Cisneros, B.J.; Kim, Y.; Pramanik, A.; Mehta, P.; Olaniyan, O. (Wiley, 2020)
There is a proactive interest in recovering water, nutrients and energy from waste streams with the increase in municipal wastewater volumes and innovations in resource recovery. Based on the synthesis of wastewater data, this study provides insights into the global and regional “potential” of wastewater as water, nutrient and energy sources while acknowledging the limitations of current resource recovery opportunities and promoting efforts to fast-track highefficiency returns. The study estimates suggest that, currently, 380 billion m3 (m3 = 1,000 L) of wastewater are produced annually across the world which is a volume fivefold the volume of water passing through Niagara Falls annually. Wastewater production globally is expected to increase by 24% by 2030 and 51% by 2050 over the current level. Among major nutrients, 16.6 Tg (Tg = million metric ton) of nitrogen are embedded in wastewater produced worldwide annually; phosphorus stands at 3.0 Tg and potassium at 6.3 Tg. The full nutrient recovery from wastewater would offset 13.4% of the global demand for these nutrients in agriculture. Beyond nutrient recovery and economic gains, there are critical environmental benefits, such as minimizing eutrophication. At the energy front, the energy embedded in wastewater would be enough to provide electricity to 158 million households. These estimates and projections are based on the maximum theoretical amounts of water, nutrients and energy that exist in the reported municipal wastewater produced worldwide annually. Supporting resource recovery from wastewater will need a step-wise approach to address a range of constraints to deliver a high rate of return in direct support of Sustainable Development Goals (SDG) 6, 7 and 12, but also other Goals, including adaptation to climate change and efforts in advancing “netzero” energy processes towards a green economy.